2013
DOI: 10.1371/journal.pone.0054112
|View full text |Cite
|
Sign up to set email alerts
|

A Laterally Acquired Galactose Oxidase-Like Gene Is Required for Aerial Development during Osmotic Stress in Streptomyces coelicolor

Abstract: Phylogenetic reconstruction revealed that most Actinobacterial orthologs of S. coelicolor SCO2837, encoding a metal-dependent galactose oxidase-like protein, are found within Streptomyces and were probably acquired by horizontal gene transfer from fungi. Disruption of SCO2837 (glxA) caused a conditional bld phenotype that could not be reversed by extracellular complementation. Studies aimed at characterising the regulation of expression of glxA showed that it is not a target for other bld genes. We provide evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…cslA appears to be the first gene of a bicistronic operon that also includes glxA , encoding a galactose oxidase required for proper aerial development during osmotic stress. Although the two genes are cotranscribed, glxA is also expressed from an independent promoter within the clsA coding sequence (33). …”
Section: Resultsmentioning
confidence: 99%
“…cslA appears to be the first gene of a bicistronic operon that also includes glxA , encoding a galactose oxidase required for proper aerial development during osmotic stress. Although the two genes are cotranscribed, glxA is also expressed from an independent promoter within the clsA coding sequence (33). …”
Section: Resultsmentioning
confidence: 99%
“…GlxA is a newly characterized member of the AA5 family of mono-copper oxidase possessing a Tyr-Cys cross-linked redox cofactor (30). A glxA null mutant blocks development and abolishes pellet formation coinciding with the loss of glycan deposition at hyphal tips, the same phenotype as observed with the cslA deletion (30,33). This is consistent with a model whereby CslA and GlxA cooperatively function in glycan deposition at the hyphal tip and are jointly responsible for the formation of reproductive aerial structures and, in liquid environments, for the formation of pellets (30).…”
mentioning
confidence: 92%
“…However, the physiological role of this protein remains elusive. Recently, Liman et al (2013) reported that Glx is required for aerial hyphae formation and for their further differentiation into hyphal spores in Streptomyces coelicolor . Similarly, this protein might play an important role in plant cell differentiation or in morphological changes.…”
Section: Resultsmentioning
confidence: 99%